Role of Entrepreneurship Training on Farmers' Intentions and Performance - Mariam Ally Tambwe (Journal of International Trade, Logistics and Law)
This paper examines the effect of entrepreneurship training on orange farmers entrepreneurial intention and performance. The theory of planned behaviour (TPB) was adopted to test the interactional effect between entrepreneurship training and TPB constructs (attitudes, subjective norms, perceived behaviour control and entrepreneurial intention. The study’s intentional entrepreneurship training model was built showing several relationships between entrepreneurship training, attitudes, subjective norms, perceived behaviour control, entrepreneurial intention and performance. The survey was conducted to 245 small scale orange farmers in Muheza. To test the model, the study’s constructs were validated followed by factor analysis and structural equation modelling. Results show the significant influence of entrepreneurship training in the development of orange farmers’ entrepreneurial intention. Further, the findings validate the developed entrepreneurship training model and enhances the body of knowledge by highlighting the key skills required by farmers in entrepreneurship training programmes.